CD33‐Targeted Therapies: Beating the Disease or Beaten to Death?. (1st September 2020) - Maakaron, Joseph E.; Rogosheske, John; Long, Meixiao; Bachanova, Veronika; Mims, Alice S.
Abstract: CD33 is a transmembrane protein that is found on cells of myeloid lineage. It is also intensely expressed on acute myeloid leukemia (AML) progenitor cells but not on normal stem cells. It internalizes on binding and dimerization, making it a specific and ideal target for AML therapeutics and drug delivery. Several targeted therapies have been tested and many are still currently in development. Gemtuzumab ozogamicin was the first and only CD33‐directed antibody‐drug conjugate to be US Food and Drug Administration approved for AML. Other targeted agents have not achieved such success. Promising new strategies include cellular therapy mechanisms and linker molecules. This is an exciting target that requires a considerable amount of precision to yield clinical benefit.